INFRASTRUCTURE AS IMPORTANT DETERMINANT OF TOURISM DEVELOPMENT IN THE COUNTRIES OF SOUTHEAST EUROPE - JOVANOVIĆ, Sonja; ILIĆ, Ivana (Ecoforum Journal, 2016)
Tourism infrastructure is the basis of tourism development and utilization of existing destination resources. Tourism infrastructure includes a large number of services, necessary to meet the needs of tourists and increase satisfaction during their stay at the destination. The subject of this paper is the consideration of relationship between the available infrastructure and the achieved level of tourism development. The paper suggests that future tourism development depends on intensive investment in infrastructure and its modernization, as an important factor of development of the tourism sector. The aim of the paper is to analyze the correlation between tourism competitiveness in the Southeast Europe (SEE) countries and the level of competitiveness of tourism infrastructure. It is noted that increase in the number of hotel rooms is a factor that largely contributes to increase in the level of tourism competitiveness of the observed group of countries.